The Influence of Mobile Legends Games in Speaking Performance among Junior High School Students in Samarinda - Darmawansyah, Darmawansyah; Khatimah, Khusnul (INTERACTION: Jurnal Pendidikan Bahasa, 2024)
The rapid advancement of technology and the pervasive use of the internet have significantly impacted various sectors, including education. This study explores the effectiveness of the online game Mobile Legends: Bang Bang in enhancing English language skills among Junior High School students in Samarinda. The game, a popular Multiplayer Online Battle Arena (MOBA) with features like voice and quick chat, provides an immersive environment for practicing English conversation. A quantitative method was employed, utilizing a closed-ended questionnaire to assess students' perceptions of the game's impact on their fluency, vocabulary, pronunciation, and grammar skills. The findings indicate that a majority of students believe Mobile Legends: Bang Bang contributes positively to their English language development. Specifically, the game aids in vocabulary acquisition, with students reporting an increase in their vocabulary and its applicability in daily life. Additionally, the interactive nature of the game helps improve pronunciation and sentence construction, offering practical language practice in a dynamic context. Overall, the study supports the potential of integrating Mobile Legends: Bang Bang as an educational tool to enhance student engagement and foster language proficiency.